GaAs Fabry‐Pérot cavity photoconductors: switching with picojoule optical pulses. Issue 3 (1st January 2013) - Peytavit, E.; Formont, S.; Lampin, J.‐F.
Abstract : It is shown that low‐temperature‐grown GaAs photoconductors using a Fabry‐Pérot cavity are very efficient optical switches in comparison with planar photoconductors. A switching efficiency of about 60% was measured with a pulse energy as low as 1.2 pJ and about 100% efficiency is achieved with a pulse energy of 14.2 pJ. Efficient optical sampling of microwave signals is now achievable with a low power pulsed laser.